Political vocabularies: FDR, the clergy letters, and the elements of political argument - Stuckey, Mary E. (Rhetoric and Public Affairs Ser, 2018)
Intro -- Contents -- Acknowledgments -- Author's Note -- Sample Letter to the Clergy -- Introduction -- Chapter 1. By Benefit of Clergy: Authoritative Political Vocabularies -- Chapter 2. Witnessing Politics: The Depictive Element of Political Vocabularies -- Chapter 3. Revelations: Naturalizing Hierarchies in Political Vocabularies -- Chapter 4. The American Eden: Mythic Elements of Political Vocabularies -- Chapter 5. Making a City on a Hill: Political Vocabularies and National Policy -- Conclusion -- Notes -- Bibliography -- Index.